Religiousnes in transition process – the concept of deconversion Heinz Streib’s - NOWOSIELSKI, MIROSŁAW ROMUALD (Studia Psychologica: Theoria et praxis, 2015)
A characteristic feature of religiosity is transformation, one aspect of which is moving away by the individual from the prior way of experiencing it’s relation to the sacred. The article presents H. Streib’s concept of deconversion. Theoretical background of it is the concept of conversio and changes in it’s understanding within the psychology. Authors present the criteria-dimensions of deconversion proposed by Streib, place the phenomenon in the context of human lifecoure, and it’s typologies, developed on the basis of theoretical analysis and qualitative research carried out by the author of the concept. The article concludes with a critical analysis of the concept. Theory of deconversion has great heuristic potential, important in the face of current research needs related to a variety of changes in the social and individual religiosity.